How common are credit-less recoveries? Firm-level evidence on the role of financial markets in crisis recovery - Ayyagari, Meghana; Demirgüç-Kunt, Asli; Maksimovic, Vojislav (Journal of Corporate Finance, 2021)
We study firm recoveries from systemic sudden stops in developing countries, where firms' cash flows suffer exogenous shocks. Contrary to macro studies suggesting that output recovery precedes that of the financial sector, firm-level data shows that only in less than a third of firms, operating cash flows recover without a recovery in external credit, and even these firms have access to other sources of cash. Specifically, firms with high prior short-term debt exposure do experience a sharp reduction in short-term credit but increase operating cash flows during a crisis. Firms with high prior cash holdings experience negative cash flows and deplete their cash holdings. Thus, firms' financial prepositioning predicts recovery in cash flows and is consistent with trade-off theories of capital structure and with precautionary motives for cash holdings. We find no support for the maturity mismatch hypothesis, which predicts that firms with high short-term debt should have harder recoveries post crisis.